Didactic impact of educational robotics on the development of STEM competence in primary education: a systematic review and meta-analysis - Irene Trapero-González; Francisco Javier Hinojo-Lucena; José-María Romero-Rodríguez; Alejandro Martínez-Menéndez (Frontiers in Education)
As robotics become increasingly present in about every area of the human daily life scheme, their presence in the educational world has become increasingly common, especially with regard to earlier stages and in relation to disciplines framed within the Science, Technology, Engineering, and Mathematics (STEM) concept, given its innate links to these programmable companions. Consequentially, the main objective of this study is to analyze the evolution in time of robotic learning mediation of STEM-based teaching and learning in the Primary Education stage. To achieve this objective, a systematic review of the literature and a meta-analysis were conducted to retrieve experiences of interest (n = 13; n = 8). The present study indicates that, despite certain hiatuses, this educational research field has been of global increasing interest, implementing a variety of robotic-related products that, in the end, have been reported to cause a moderate benefit regarding the acquisition and strengthening of STEM competences. Future research lines are discussed, pointing to the urgent need to establish a framework of reference for didactic planning around these resources in order to extend their use to every potential teacher in the target stage.